The effect of store atmosphere on impulse buying with hedonic shopping motivation as mediation variable (at mis glam cosmetics shop in padang city) - Febby Alexandra; Yasri (Universitas Negeri Padang, 2021)
The purpose of this research is to examine: (1) The Effect of Store Atmosphere on Impulse Buying at Miss Glam cosmetics store (2) The Effect of Store Atmosphere on Hedonic Shopping Motivation at Miss Glam cosmetics store (3) The Effect of Hedonnic Shoppings Motivations on Impulse Buying for cosmetic stores. Miss Glam in Padang City. This type of research is a quantitative research. The population of this research is all customers of Miss Glam Cosmetics Shop in Padang City. In selecting the sample, the method used is the non-probability method with a total sample of 189 respondents. The research uses primary data obtained by submitting questionnaires to all customers of the Miss Glam Cosmetics Shop in Padang City. The analytical method used is Structural Equation Modeling (SEM) through SmartPLS software. The results of this study are: (1) Store Atmosphere has a significant effect on Impulse Buying at the Miss Glam Cosmetics Store in Padang City (2) Store Atmosphere has a significant effect on Hedonic Shopping Motivation at Miss Glam Cosmetics Tok.o in Padang City (3) Hedonic Shopping Motivation has a significant effect on Impulse Buying at the Miss Glam Cosmetics Store in Padang City.